Teaching Direct and Inverse proportion to 5th Grade Students through Pictures and Real-Life Problems, Leading Towards Autonomous Learning - Tabassum Saleem, Surayya Mukhtar Shamsa Aziz (JSE, 2023)
Mathematical concepts of ratio and proportions are primarily included in the mathematics syllabus at the 5th-grade level. The concept of proportion is quite tricky for students. Most of the questions based on the concept of proportion are in the form of word problems.